2021
DOI: 10.3390/land10020094
|View full text |Cite
|
Sign up to set email alerts
|

Land Suitability Evaluation for Wild-Simulated Ginseng Cultivation in South Korea

Abstract: Wild-simulated ginseng (WSG) is highly sensitive to growth conditions. Nevertheless, the suitability evaluation of actual WSG cultivation sites for a sustainable yield has not been conducted in South Korea, nor at a global level. This study aimed to evaluate the suitability of actual WSG cultivation sites to understand the status of these sites and to present a methodology that can be applied to the determination of WSG cultivation sites by combining the major factors essential for WSG growth. Suitability was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…The pH was initially neutral and rose to 8.22 on day 11 due to aerobic waste breakdown. The alkaline nature of pH could be caused by a drop in carbonic acids (H 2 CO 3 ) and bicarbonate ions (HCO 3 − ), which leads to the consumption of H + ions (Kim, 2005). Another research on the aerobic study reported the same pH range of 7.0-9.0 (Nag et al, 2018).…”
Section: Treatability Study Under Aerobic and Anaerobic Conditionsmentioning
confidence: 99%
“…The pH was initially neutral and rose to 8.22 on day 11 due to aerobic waste breakdown. The alkaline nature of pH could be caused by a drop in carbonic acids (H 2 CO 3 ) and bicarbonate ions (HCO 3 − ), which leads to the consumption of H + ions (Kim, 2005). Another research on the aerobic study reported the same pH range of 7.0-9.0 (Nag et al, 2018).…”
Section: Treatability Study Under Aerobic and Anaerobic Conditionsmentioning
confidence: 99%